Hidradenoma Papilliferum - Kaoutar Laamari; Hanane Baybay; Samia Mrabat; Zakia Douhi; Sara Elloudi (Dermatology, 2020)
A 45-year-old female patient presented with an asymptomatic nodule of 6-months duration in the vulva. On examination, a well-circumscribed nodule of size 1 cm was seen on inner aspect of left labium majus (Figure 1). The nodule was firm and non-tender. Dermoscopy showed pink and white structures with curvilinear vessels (Figures 2 and 3). Differential diagnoses considered were hidradenoma papilliferum or some other adnexal tumor, pyogenic granuloma, and a remote possibility of donovaniosis or amelanotic melanoma. The nodule was excised and sent for histopathological examination, which showed a dermal tumor with cells in papillary folds, tubules, and cystically dilated spaces. These findings were those of hidradenoma papilliferum.